2014
DOI: 10.1002/2014jf003196
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of fluvial channels for paleorock uplift rates in Taiwan

Abstract: The transient response of erosion to changes in rock uplift rate leads to the preservation of rock uplift history in the long profiles of rivers. However, extracting this information is nontrivial as changes in channel steepness are the result of both spatial and temporal changes in rock uplift rate, as well as other factors such as climate and rock type. We exploit an analytical linear solution for river channel profile evolution in response to erosion and tectonic uplift to investigate the rock uplift histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
126
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 132 publications
(186 reference statements)
1
126
0
Order By: Relevance
“…The ratio m/n is also used to describe the relationship between slope and drainage area in describing stream long profiles (Flint, 1974). All models using SPIM, including studies on drainage reorganization and stability , tectonic histories of landscapes (Goren et al, 2014b;Fox et al, 2014), and persistent drainage migration (Pelletier, 2004), involve the specification of this ratio. In addition, the specific values of m and n are important (Tucker and Whipple, 2002).…”
Section: Introductionmentioning
confidence: 91%
“…The ratio m/n is also used to describe the relationship between slope and drainage area in describing stream long profiles (Flint, 1974). All models using SPIM, including studies on drainage reorganization and stability , tectonic histories of landscapes (Goren et al, 2014b;Fox et al, 2014), and persistent drainage migration (Pelletier, 2004), involve the specification of this ratio. In addition, the specific values of m and n are important (Tucker and Whipple, 2002).…”
Section: Introductionmentioning
confidence: 91%
“…4). Only basins draining ≥ 3 km 2 were analyzed because it has been shown that ephemeral streams, such as those on Crete, have difficulty responding to tectonic forcing at small drainage areas (e.g., Frankel and Pazzaglia, 2005). We delineated 21 drainage basins and labeled them 1 to 21 from west to east (Fig.…”
Section: Topographic Analysesmentioning
confidence: 99%
“…Simulating nuclide concentrations in settings where denudation rates vary in space and time is possible (Mudd, 2016), but computationally intensive and one must have some confidence that one can accurately reconstruct the temporal evolution of denudation rates. Although recent progress has been made in deriving time series of denudation rates from current topography (e.g., Whittaker et al, 2008;Pritchard et al, 2009;Hurst et al, 2013;Goren et al, 2014;Fox et al, 2014;Croissant and Braun, 2014;Rudge et al, 2015), these methods still suffer from the fact that we lack devices for time travel and struggle to test such reconstructions.…”
Section: Uncertainties Introduced By Spatial and Temporal Variabilitymentioning
confidence: 99%